Comparative Efficacy of Daratumumab Monotherapy and Pomalidomide Plus Low‐Dose Dexamethasone in the Treatment of Multiple Myeloma: A Matching Adjusted Indirect Comparison. (30th November 2017) - Van Sanden, Suzy; Ito, Tetsuro; Diels, Joris; Vogel, Martin; Belch, Andrew; Oriol, Albert
Abstract : Background: Daratumumab (a human CD38‐directed monoclonal antibody) and pomalidomide (an immunomodulatory drug) plus dexamethasone are both relatively new treatment options for patients with heavily pretreated multiple myeloma. A matching adjusted indirect comparison (MAIC) was used to compare absolute treatment effects of daratumumab versus pomalidomide + low‐dose dexamethasone (LoDex; 40 mg) on overall survival (OS), while adjusting for differences between the trial populations. Materials and Methods: The MAIC method reduces the risk of bias associated with naïve indirect comparisons. Data from 148 patients receiving daratumumab (16 mg/kg), pooled from the GEN501 and SIRIUS studies, were compared separately with data from patients receiving pomalidomide + LoDex in the MM‐003 and STRATUS studies. Results: The MAIC‐adjusted hazard ratio (HR) for OS of daratumumab versus pomalidomide + LoDex was 0.56 (95% confidence interval [CI], 0.38–0.83; p  = .0041) for MM‐003 and 0.51 (95% CI, 0.37–0.69; p  < .0001) for STRATUS. The treatment benefit was even more pronounced when the daratumumab population was restricted to pomalidomide‐naïve patients (MM‐003: HR, 0.33; 95% CI, 0.17–0.66; p  = .0017; STRATUS: HR, 0.41; 95% CI, 0.21–0.79; p  = .0082). An additional analysis indicated a consistent trend of the OS benefit across subgroups based on M‐protein level reduction (≥50%, ≥25%, and <25%). Conclusion: The MAIC results suggest that daratumumab improves OS compared with pomalidomide + LoDex in patients with heavily pretreated multiple myeloma. Implications for Practice: This matching adjusted indirect comparison of clinical trial data from four studies analyzes the survival outcomes of patients with heavily pretreated, relapsed/refractory multiple myeloma who received either daratumumab monotherapy or pomalidomide plus low‐dose dexamethasone. Using this method, daratumumab conferred a significant overall survival benefit compared with pomalidomide plus low‐dose dexamethasone. In the absence of head‐to‐head trials, these indirect comparisons provide useful insights to clinicians and reimbursement authorities around the relative efficacy of treatments. Abstract : Outcomes remain poor in patients with relapsed and refractory multiple myeloma. This article compares the overall survival of daratumumab monotherapy with pomalidomide plus low‐dose dexamethasone in patients with heavily treated multiple myeloma using a matching adjusted indirect comparison technique.